Asking sensitive questions using the unmatched count technique: Applications and guidelines for conservation. Issue 3 (8th January 2019) - Hinsley, Amy; Keane, Aidan; St. John, Freya A. V.; Ibbett, Harriet; Nuno, Ana
Abstract: Researchers and practitioners are increasingly using methods from the social sciences to address complex conservation challenges. This brings benefits but also the responsibility to understand the suitability and limitations of these methods in different contexts. After years of use in other disciplines, the unmatched count technique (UCT) has recently been adopted by conservation scientists to investigate illegal and socially undesirable human behaviours. Here we provide guidance for practitioners and researchers on how to apply UCT effectively, and outline situations where it will be the most and least appropriate. We reviewed 101 publications in refereed journals that used UCT to draw conclusions on its use to date and provide recommendations on when and how to use the method effectively in conservation. In particular, we explored: type of studies undertaken (e.g. disciplines; behaviour being studied; rationale for using UCT); survey administration (e.g. sample size, pilot studies, administration mode); UCT outcomes (e.g. type of analyses, estimates, comparison with other methods); and type of recommendations. We show that UCT has been used across multiple disciplines and contexts, with 10 studies that focus on conservation and natural resource use. The UCT has been used to investigate topics falling into five categories: socially undesirable behaviours, socially undesirable views, illegal or non‐compliant behaviours, socially desirable behaviours; and personal topics (e.g. being HIV positive). It has been used in 51 countries and is suitable to several situations, but limitations do exist, and the method does not always improve reporting of sensitive topics. We provide best‐practice guidance to researchers and practitioners considering using UCT. We highlight that alternate methods should be considered if sample sizes are likely to be small, the behaviour in question is likely to be extremely rare, or if the behaviour is not particularly sensitive. UCT can be a useful tool for estimating the extent of non‐compliance within a conservation context, but as with all scientific investigation, careful study design, robust sampling and consistent implementation are required in order for it to be effective.